Effects of Cd and Paper Dictionaries on Reading Comprehension: Qualitative and Quantitative Analyses - Kon, Mooi Foon (1999)
In this era that emphasizes electronic and digital technologies, dictionaries which have long been an important learning tool have taken a new form. Electronic references that aid in understanding texts are rapidly being produced and more easily available. Such electronic references may present a learning environment that is totally different from the present. Hence, there is a need to investigate the two different media of dictionary use: compact disc and paper form in terms of similarities and differences. In this exploratory study, the qualitative analysis analysed the content and presentation format of the two types of dictionary and students' preference over them. Students' behaviour during the compact disc dictionary (CDD) use was also observed The quantitative analysis focussed on how useful the CDD was as compared to the paper dictionary (PD) in aiding reading comprehension among frrst-year undergraduates at Universiti Putra Malaysia. Results from the qualitative analysis showed that both the CDD and PD were not similar in terms of content and presentation format Certain features were absent in the CDD but present in the PD and vice versa. Moreover, the treatment of words was different in both the dictionaries. The presentation format also differed. It was also discovered that students preferred the CDD to the PD. There was no correlation between computer literacy and scores in the reading comprehension tests. In addition, students who were computer literate did not show their preference for the CDD. This resulted in the "no correlation" between computer literacy and preference for the CDD. The findings from the quantitative measurement revealed no significant difference in reading comprehension tests between students who used the CDD as compared to students who used the PD. In spite of the no significant difference, this study proved that both CDD and PD helped students in reading comprehension. Quantitative analyses found that students who used either the CDD or the PD performed far better than those who did not use any dictionaries. Although both media had their strengths and weaknesses, they should coexist to suit students' needs and convenience. Hence, dictionary use should be prioritized and encouraged by students in their pursuit of language proficiency attainment.